2017
DOI: 10.1155/2017/7302081
|View full text |Cite
|
Sign up to set email alerts
|

First Integrals and Hamiltonians of Some Classes of ODEs of Maximal Symmetry

Abstract: Complete sets of linearly independent first integrals are found for the most general form of linear equations of maximal symmetry algebra of order ranging from two to eight. The corresponding Hamiltonian systems are constructed and it is shown that their general solutions can also be found by a simple superposition formula from the solutions of a scalar second-order source equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…More recently, Krause and Michel [16] proved the converse of this result in the case of linear equations and showed that in fact a linear scalar equation is of maximal symmetry if and only if it is iterative. Some recent results have also been obtained about linear scalar equations of maximal symmetry, concerning their transformation properties [17,18], their coefficient characterization [19,20,17], their first integrals or Hamiltonian forms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Krause and Michel [16] proved the converse of this result in the case of linear equations and showed that in fact a linear scalar equation is of maximal symmetry if and only if it is iterative. Some recent results have also been obtained about linear scalar equations of maximal symmetry, concerning their transformation properties [17,18], their coefficient characterization [19,20,17], their first integrals or Hamiltonian forms [21,22].…”
Section: Introductionmentioning
confidence: 99%